The different outcomes between breast-conserving surgery plus radiotherapy and mastectomy in metaplastic breast cancer: A population-based study. - Lin-Yu Xia (Public Library of Science (PLoS), 2021)
Background Metaplastic breast cancer (MBC) are rare. The survival outcomes of MBC patients after breast conserving surgery plus radiotherapy (BCS+RT) or mastectomy have not been established. The study aimed to compare survival outcomes of MBC patients subjected to BCS+RT or mastectomy therapeutic options. Methods Patients who were subjected to BCS+RT or mastectomy between 2004 and 2014 were enrolled in this study through the Surveillance, Epidemiology and End Results (SEER) database. Breast cancer-specific survival (BCSS) and the overall survival (OS) of the participants were determined. Cox proportional hazard model and the Kaplan Meier method were used to determine the correlation between the two surgical methods and survival outcomes. Results A total of 1197 patients were enrolled in this study. Among them, 439 patients were subjected to BCS+RT, while 758 patients were subjected to mastectomy. After propensity score matching (PSM), the BCS+RT and mastectomy groups consisted of 321 patients, respectively. The univariate and multivariate analysis with a 6-month landmark all indicate that patients receiving BCS+RT has higher OS than patients receiving mastectomy (HR = 0.701,95% CI = 0.496-0.990, P = 0.044; HR = 0.684,95% CI = 0.479-0.977, P = 0.037) while the BCSS was no difference between the two groups (HR = 0.739,95% CI = 0.474-1.153, P = 0.183; HR = 0.741,95% CI = 0.468-1.173, P = 0.200). Conclusion The BCS+RT therapeutic option exhibits a higher OS in MBC patients compared to the mastectomy approach.